Perubahan Kadar Komponen Kimia Bambu Andong akibat Perlakuan Steam (Change of Chemical Components Content in Andong Bamboo due to Steam Treatment) - Muhammad I Maulana; Deded S Nawawi; Nyoman J Wistara; Rita K Sari; Siti Nikmatin; Sena Maulana; Se-Hwi Park; Fauzi Febrianto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2018)
Steam and rinsing treatment with water and 1% NaOH solution of andong bamboo strands have been known to improve physical and mechanical properties of its oriented strand board (OSB). The improvement of bamboo OSB properties might be caused by the change of  chemical components content during steam and rinsing process. This study aims to measure the changes of chemical components content in andong bamboo (Gigantochloa pseudoarundinacea) due to steam treatment and rinsing with water or sodium hydroxide solution. Samples was taken from andong bamboo stem without bark and node part. The treatments of samples were steam at 126 ° C for 1 hour, steam and rinsing with water, and, steam and rinsing with 1% NaOH, respectively. Air-dried samples were, then, subjected to mill in order to get 40-60 mesh particles size, which was used for  chemical components analyses. The results showed that steam and rinsing with water or 1% NaOH solution treatment reduced hemicellulose and extractive contents (dissolved in cold water, hot water, ethanol-benzene and NaOH 1% solution), whereas alpha-cellulose and lignin were relatively stable. Steam and rinsing treatment generally increased the pH value of bamboo samples.